(untitled) (Research, Society and Development, 2021)
Paleontology is the study of the evolution of life on Earth through the records left by the organisms, explaining the changes and dispersion of them as well as the modifications of the planet throughout its geological history. In view of this importance, an importantally in the process of disseminating this knowledge is the Didactic Book, material of a pedagogical nature that helps in approaching knowledge in class in a didactic way. Considering the above, the objective of this work is to investigate the approach of the theme “paleontology” in collections of scientific textbooks from the final years of elementary school. This work has a qualitative and quantitative character in the case of bibliographic research, which consisted of the analysis of Didactic Books of science in the final years of elementary school, in the municipality of Uruguaiana, Rio Grande do Sul. The results analyzed denote a devaluation of paleontology in the materials due to the superficial, incomplete or absent approach to these issues. It was concluded that it is necessary to legitimize paleontology by Didactic Books in their collections, considering the importance of this theme in the articulation in different contents of natural sciences, as well as among the other curricular disciplines.